A Queer (Beginning to the) Bible - West, Gerald O. (Concilium, 2019)
Genesis is the starting point for an African queer biblical trajectory in this article. Locating queer African bodies as subjects of interpretation of the Bible, this article demonstrates how the book of Genesis has been used within actual African contexts to recognize a queer trajectory in scripture. The Bible, we argue, is a site of struggle, with contending trajectories/voices, some of which are queer, particularly when read from LGBTIQA+ African social locations.